The Influence of the Physical and Non-Physical Work Environment on Employee Job Satisfaction at PT Talenta Bumi in Barito Kuala Regency - Nina Anggiri Yani; Fitriyadi; Saladin Ghalib; Setio Utomo (Journal of Business Transformation and Strategy, 2025)
This study aims to determine and examine the effect of Physical Work Environment and Non-Physical on Employee Job Satisfaction at PT TALENTA BUMI in Barito Kuala District. This study used a quantitative approach with a sample of 113 respondents with data collection techniques using questionnaires and data analysis using multiple linear regression with the help of SPSS Statistics version 26. The results showed that physical work environment had a significant effect on employee job satisfaction and non-physical work environment had a significant effect on employee job satisfaction. The variable of physical work environment and non-physical together had a significant effect on employee job satisfaction